2018
DOI: 10.1111/tpj.14122
|View full text |Cite
|
Sign up to set email alerts
|

The proof is in the bulb: glycerol influences key stages of lily development

Abstract: A bulb is a whole plant condensed into an underground organ. A geophyte's bulb comprises both food reserves and important developmental history that may affect its whole growth. In Easter lily (Lilium longiflorum), bulb size is associated with the plant's flowering pathwayvernalization or photoperiodand also affects sprouting, flower quality and abortion rate. The aim of this study was to investigate the reasons for the major physiological differences between large and small bulbs. Lily bulbs start their devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 122 publications
0
16
0
Order By: Relevance
“…However, it is likely that the molecular mechanism of vernalization and its role in flowering adjustment is quite different. In Arabidopsis , the winter cold is mainly required to down‐regulate FLC ( Flowering Locus C ) flowering repressor (Bouché et al ., 2017; Antoniou‐Kourounioti et al ., 2018; Hepworth et al ., 2018), while the molecular mechanisms of vernalization are different in bulbous taxa (Lee et al ., 2013; Lazare et al ., 2019; Wang et al ., 2019). However, it was also suggested that increased auxin sensitivity of the bulb induced by a long cold period is a critical common element for the vernalization of several bulbous taxa (Khodorova & Boitel‐Conti, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that the molecular mechanism of vernalization and its role in flowering adjustment is quite different. In Arabidopsis , the winter cold is mainly required to down‐regulate FLC ( Flowering Locus C ) flowering repressor (Bouché et al ., 2017; Antoniou‐Kourounioti et al ., 2018; Hepworth et al ., 2018), while the molecular mechanisms of vernalization are different in bulbous taxa (Lee et al ., 2013; Lazare et al ., 2019; Wang et al ., 2019). However, it was also suggested that increased auxin sensitivity of the bulb induced by a long cold period is a critical common element for the vernalization of several bulbous taxa (Khodorova & Boitel‐Conti, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors, such as for example the day length, affect bulb enlargement and taste eminence in onion [33]. In onion, light range and quality impacts bulb formation and quality [34][35][36][37][38][39][40][41]. The bulb initiation and growth of further Allium species including garlic have been shown to be influenced by day length, temperature, and carbohydrates [42,43].…”
Section: Photoperiodic Control In Bulb Enlargementmentioning
confidence: 99%
“…In L. longiflorum, cold exposure is not an obligatory prerequisite for flowering, as an alternative flowering pathway can bypass vernalization in small bulbs (Lazare and Zaccai, 2016). Recently, the levels of glycerol in L. longiflorum bulbs was found to be associated with a delay in sprouting and flowering time and a reduction in abortion rate (Lazare et al, 2019).…”
Section: Introductionmentioning
confidence: 99%